W. C. Handy's blues an anthology ; complete words and music of 70 great songs and instrumentals - Handy, W. C. 1873-1958 (Dover Publ., 2012)
This classic collection consists of 70 melodies arranged for piano and voice by W. C. Handy. Extensive supplements include notes for each song, a bibliography, and eight striking illustrations by Miguel Covarrubias. Historical text by music critic Abbe Niles, plus two Introductions describing the book's publication history and Handy's life and career
Keywords: Blues (Music); Song; Blues; Anthologie